The Influence Of Health Education Counseling Methods On Knowledge Of Preconceptional Nutrition On Future Bride - Nara Lintan Mega Puspita; Meirna Eka Fitriasnani; Huda Rohmawati; Kurnia Novitasari; Dwi Ayu Lestari; Ihrom Fatma Saputri (Journal of Global Research in Public Health, 2023)
Nutritional status during the preconception period is one of the determinants of the smooth process of pregnancy to delivery. The premarital period can be associated with the preconception period. The purpose of this research is to determine the effect of health education counseling methods on knowledge about preconception nutrition On Future Bride.This study used the one-group pretest-posttest design method. The sample in this study was 16 respondents taken using a non-probability sampling technique. The research instruments used were counseling methods and questionnaires. The research results were analyzed using the Wilcoxon statistical test. The results of the research showed that p-value was 0.001 < α (0.05) so there is an influence of health education counseling methods on knowledge about preconception nutrition in prospective brides. It is hoped that health workers can become a reference for applying health education for prospective brides about preconception nutrition as a means to increase knowledge.